Beginner Voter Perception of Presidential Candidates (Case Study of the Presidential Election in 2019) - Syahrur Razy; Winarno Winarno; Rusnaini Rusnaini (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
In the 2019 general election, the Indonesian people simultaneously elected the President and Vice President and legislative members. The Indonesian people are waiting for who will lead the next five years, especially for the President and Vice President with figures Joko Widodo - Ma'ruf Amin and challenger Prabowo Subianto - Sandiagan Uno. This study aims to determine the perceptions of first-time voters in the two-figure Presidential election in 2019. This study uses a quantitative descriptive study, data obtained from the sample of the study population were analyzed according to the statistical methods used. Descriptive research in this study is intended to get the perception of novice voters at SMAN 5 Surakarta of the presidential candidates in the 2019 general election. There are several things that can affect perceptions about the figure of the President, namely leadership, anti-corruption, welfare, nationalism and change for a more Indonesian state good. All factors are obtained through social media owned by novice voters. Beginner voters in SMAN 5 Surakarta are in the category of critical voters because with knowledge of social media and issues in the media are able to assess whether the prospective leader is eligible to be elected in the general election.